CORPORATE CHARACTERISTICS AND ISLAMIC SOCIAL REPORTING: AN EMPIRICAL ANALYSIS OF SHARIA-COMPLIANT FIRMS - Kaswoto, Junet; Fitriana, Amalia Indah; Apriliyana, Vertian; Haziqi, Muhammad Hassan (Dynamic Management Journal, 2025)
This study examines the influence of firm size, profitability, and leverage on Islamic Social Reporting (ISR) disclosure among companies listed on the Jakarta Islamic Index (JII) from 2017 to 2021. As demand for transparency and social accountability grows in Islamic economies, understanding the determinants of ISR disclosure becomes crucial. Using a quantitative approach and panel data regression analysis (EViews 12), the study employs purposive sampling to select 12 firms (60 observations). Findings reveal that firm size has a significant positive effect on ISR disclosure, while profitability and leverage are not significant. However, collectively, these variables significantly influence ISR disclosure. The study contributes to the literature by providing empirical evidence on corporate social reporting in an emerging Islamic capital market. Its novelty lies in focusing on ISR disclosure within the JII context, where research remains limited. Results offer practical insights for regulators and corporate managers aiming to enhance Islamic social accountability through strategic financial and organizational policies.